Fig Wax Scale, Ceroplastes rusci (L.) (Insecta: Hemiptera: Coccoidea: Coccidae) - Avas B. Hamon; Gregor J. Mason (EDIS)
The fig wax scale, Ceroplastes rusci (L.), was first discovered in Florida at several nursery and stock dealers in 1994 and 1995. It has been a pest of Ixora spp. and infrequently found on other host plants. Prior to these discoveries, the California Department of Food and Agriculture had intercepted specimens from Florida. This document is EENY-187 (originally published as DPI Entomology Circular 380), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2001.